Bipotent mammary stem cells: now in amazing 3D - van Amerongen, Renée (BioMed Central, 2014)
For many decades, developmental biologists and cancer researchers alike have been trying to understand the relationship between the basal and luminal cell compartments in the mouse mammary epithelium. Delineating the mammary stem and progenitor cell hierarchy will provide fundamental knowledge of how cell proliferation and differentiation are orchestrated to build, maintain and regenerate a complex mammalian tissue. Moreover, it is expected to offer insight into the cells of origin for human breast cancer. A new lineage-tracing study has fuelled the discussion as to the existence of bipotent stem cells in the basal layer of the mouse mammary epithelium.